Modern Aspects of the Clinic, Diagnosis and Treatment of Prediabetes - N. V. Pyrikova; I. V. Osipova; I. G. Polyakova (Архивъ внутренней медицины)
Prediabetes is a common violation of carbohydrate metabolism, the medical and social relevance of which is due to the negative impact on the incidence of type 2 diabetes mellitus (DM) and cardiovascular disease (CVD). The analyzed literature emphasizes the presence of a close pathogenetic relationship between type 2 DM/prediabetes and CVD. This relationship becomes even more relevant, taking into account, on the one hand, the persistent upward trend in the prevalence of carbohydrate metabolism disorders in the population, and on the other hand, the fact that in patients with dysglycemia it is cardiovascular complications that are the main cause of death. However, while the significance of type 2 DM as a risk factor for CVD is widely known and its presence immediately stratifies most patients to a group of high or very high cardiovascular risk, the contribution of prediabetes to the development of CVD remains underestimated among the therapeutic and cardiological communities. The high prevalence of prediabetes creates prerequisites for a further increase in the incidence of type 2 DM and CVD in the Russian Federation, which requires doctors of various specialties to be wary of early detection of prediabetes, since timely preventive measures can significantly reduce the risk of type 2 DM and its complications in the future. Currently, the effectiveness of both non-drug and drug strategies in preventing the development of type 2 DM in people with prediabetes has been confirmed, more and more data are accumulating about the possibility of effective prevention of CVD in prediabetes. According to modern research, the primary role of measures to actively change lifestyle in the treatment and prevention of prediabetes is emphasized, at the same time, the effectiveness of these measures can be reduced due to insufficient commitment of the patients themselves to their independent long-term implementation. Therefore, the strategy of prescribing metformin for the prevention of type 2 diabetes is absolutely justified if the doctor and patient recognize the inefficiency or inability to follow the recommendations for active lifestyle changes for a long time. The article presents the data on the etiology, epidemiology, diagnosis, and approaches to the management of patients with prediabetes from the standpoint of modern recommendations.